2020
DOI: 10.1364/ol.385072
|View full text |Cite
|
Sign up to set email alerts
|

On the actual spatial resolution of Brillouin Imaging

Abstract: The comprehension of the behavior of complex heterogeneous materials requires the adoption of imaging techniques to analyze spatially resolved properties. With plenty of prospects in biophysical and biomedical fields, Brillouin imaging is an emerging technique able to generate maps with mechanical contrast at microscales. As in any imaging technique a key parameter is the spatial resolution, which depends both on the control of the probe and on the physical mechanism of interaction with the sample. In particul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…0.27–0.3 cm −1 ). The simultaneous detection of two Brillouin peaks in a single spectrum suggests the coexistence of elastically different structures at micrometric length scale 25 . The longitudinal elastic modulus M of each component can be obtained from the Brillouin frequency shift ν through the relationship: where ρ is the mass density, n the refractive index and λ the wavelength of the laser source.…”
Section: Resultsmentioning
confidence: 97%
“…0.27–0.3 cm −1 ). The simultaneous detection of two Brillouin peaks in a single spectrum suggests the coexistence of elastically different structures at micrometric length scale 25 . The longitudinal elastic modulus M of each component can be obtained from the Brillouin frequency shift ν through the relationship: where ρ is the mass density, n the refractive index and λ the wavelength of the laser source.…”
Section: Resultsmentioning
confidence: 97%
“…The curve fitting routine was written in Fortran77 and was based on a damped harmonic oscillator (DHO) model including convolution with an instrumental Gaussian function [20]. Various spurious effects can cause peak broadening, such as illumination/collection geometry, absorption in strongly scattering media, multiple scattering, and the use of high NA objectives (enabling a range of q values) [31, 32]. In this work, a backscattering geometry was employed together with a small NA objective, thus minimising the effect of spurious Brillouin line broadening.…”
Section: Methodsmentioning
confidence: 99%
“…Early work has determined that Brillouin spectroscopy can probe the complete elasticity tensor and mechanical anisotropy of protein fibers (Randall et al 1979;Cusack and Miller 1979;Cusack and Lees 1984;Palombo et al 2014;Edginton et al 2016;Koski et al 2013) and has shown that the longitudinal modulus is a few orders of magnitude higher than the moduli derived from classical biophysical approaches. This discrepancy is thought to arise from the different spatial and temporal scales of the two measurements (at high and low frequencies), as well as from the different types of moduli, i.e., longitudinal modulus vs. shear and Young's moduli that are more widely used in biophysics and assumed to represent the "stiffness" or "rigidity" (Prevedel et al 2019;Edginton et al 2018;Silvia Caponi and Cavalleri 2019;Andriotis et al 2019). However, the contribution of water to both tissue biomechanics and the Brillouin spectrum is a complicating factor.…”
Section: How Sample Hydration Impacts the Brillouin Spectrummentioning
confidence: 99%